2022
DOI: 10.1093/ofid/ofac582
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Rifampin Following Debridement and Implant Retention for Staphylococcal Prosthetic Joint Infection: Is it Effective if not Combined With a Fluoroquinolone?

Abstract: Whether rifampin benefits retained staphylococcal prosthetic joint infection is unsettled. In a meta-analysis of eight studies, we found greater clinical cure with fluroquinolone-rifampin versus all other regimens (OR 2.68; 95% CI 1.43-5.02), but no greater cure with other rifampin combinations versus regimens without rifampin (OR 1.22; 95% CI 0.79-1.88).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Rifampin has been recommended as one of the therapeutic agents for the treatment of staphylococcal infections due to its potent bactericidal activity against S. aureus [ 4 , 5 , 13 , 14 ]. It has been shown to be highly effective in treating staphylococcal infections related to foreign bodies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rifampin has been recommended as one of the therapeutic agents for the treatment of staphylococcal infections due to its potent bactericidal activity against S. aureus [ 4 , 5 , 13 , 14 ]. It has been shown to be highly effective in treating staphylococcal infections related to foreign bodies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolones have been considered the best antibiotics to use in combination with rifampin for the treatment of S. aureus infections [ 4 , 5 , 19 , 20 , 21 ]. However, studies have not shown consistent synergistic effects with the combination of fluoroquinolones and rifampin, and in some studies, antagonism has been reported [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Although the role of rifampin for staphylococcal hardware infections remains unsettled, a recent expert review continued to support its use. 9,10 Case 2: Mycobacterial infection in an immunocompromised and pregnant host A 30-year-old pregnant female at 13-weeks gestation with a history of indeterminate colitis, on infliximab therapy for 2 years, and latent tuberculosis treated with 4 months of rifampin prior to initiation of infliximab, presented with 4 months of a The patient remained on fluconazole with plans to complete 12 months of therapy, and received periodic laboratory and clinical monitoring to ensure an optimal outcome (COpAT). Her persistent pulmonary nodules were thought to represent scarred granulomas and sequelae of prior infection rather than an ongoing active fungal disease.…”
Section: Case 1: Methicillin-susceptible Staphylococcus Aureus Bacter...mentioning
confidence: 99%
“…8 Although the role of rifampin for staphylococcal hardware infections remains unsettled, a recent expert review continued to support its use. 9,10…”
Section: Introductionmentioning
confidence: 99%